(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the role of the sociocultural approach in developing speaking skills in English language learning. It highlights the interconnection between language, culture, and social interaction, emphasizing that effective communication requires not only linguistic knowledge but also sociocultural competence. The study discusses the importance of authentic materials, real-life communication contexts, and interactive teaching methods in enhancing students’ speaking abilities. Furthermore, it analyzes how sociocultural factors contribute to the development of communicative competence in language learners.